Bronchial Asthma and Mucociliary Clearance - A Bidirectional Relationship - Oppova, Daša; Bánovčin, Peter; Ħ#142;urdík, Peter; Babničová, Michaela; Jeseňák, Miloš (Current Respiratory Medicine Reviews, 2024)
The integrity of the airway epithelium plays an important role in the defence against pathogens and various immunogenic stimuli from the external environment. Properly functioning mucociliary clearance is an indispensable part of the respiratory system defence and it relies on adequate viscoelastic properties of mucus, as well as the intact function of a significant number of healthy ciliated cells. The movement of the cilia can be affected by many endogenous and exogenous factors. Complex mucociliary clearance dysfunction can be seen as a part of the respiratory system inflammation. Bronchial asthma is one of the most common inflammatory diseases of the respiratory system. It is characterised by structural and functional changes in the airways. The last decades of bronchial asthma research point to asthmatic inflammation as the cause of airway remodelling with subsequent impairment of mucociliary transport function. Changes in the respiratory epithelium in patients with bronchial asthma include hypertrophy of secretory cells, overproduction of mucus, increase in mucus viscosity, decline of ciliated cells, decrease of ciliary beat frequency, and more. Cytokines of T2-high type of asthmatic inflammation, such as interleukin IL-13 and IL-4, have been shown to contribute to these changes in the airway epithelium significantly. There is strong evidence of cytokine-induced overexpression of important transcription factors, which results in hyper- and metaplasia of secretory cells and also transdifferentiation of ciliary cells. Impaired mucociliary clearance increases the risk of airway infection and contributes to the worsening of bronchial asthma control.
Keywords: mucin